Phytochemical and Larvicidal Studies on Stemona curtisii: Structure of a New Pyrido[1,2-a]azepine Stemona Alkaloid - Mungkornasawakul P. (2014)
A new pentacyclic Stemona alkaloid, stemocurtisinol (3), with a pyrido[1,2-α]azepine A,B-ring system, and the known pyrrolo[1,2-α ]azepine alkaloid oxyprotostemonine (4) have been isolated from a root extract of S. curtisii. The structure and relative stereochemistry of stemocurtisinol was determined by spectral data interpretation and X-ray crystallography. This compound is a diastereoisomer of oxystemokerrin and has the opposite configuration at C-4 and C-19. The individual alkaloid components showed significant larvicidal activity (IC50 4-39 ppm) on mosquito larvae (Anopheles minimus HO).